2021
DOI: 10.1186/s12877-020-01964-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of additional resistance and balance training in exercise-based cardiac rehabilitation in older patients after valve surgery or intervention: randomized control trial

Abstract: Background To evaluate the short- and mid-term effect of a specially tailored resistance and balance training provided in addition to usual cardiac rehabilitation (CR) care program in older patients after valve surgery/intervention. Methods Single-center (inpatient CR clinic in Lithuania) randomized controlled trial. Two hundred fifty-two patients were assessed for eligibility on the first day of admittance to CR early after (14.5 ± 5.9 days) valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…8 Overseas studies have shown that cardiac rehabilitation can reduce the all-cause mortality rate after myocardial infarction by 8-37% and the cardiovascular mortality rate by 7%-38%, which is an important factor in determining treatment and the patient's quality of life. [9][10][11][12] A randomized controlled study in China confirmed the feasibility of cardiac rehabilitation through aerobic exercise in patients with coronary heart disease. 13 Hence, increasing attention has been paid to cardiac rehabilitation after coronary heart disease intervention.…”
Section: Introductionmentioning
confidence: 99%
“…8 Overseas studies have shown that cardiac rehabilitation can reduce the all-cause mortality rate after myocardial infarction by 8-37% and the cardiovascular mortality rate by 7%-38%, which is an important factor in determining treatment and the patient's quality of life. [9][10][11][12] A randomized controlled study in China confirmed the feasibility of cardiac rehabilitation through aerobic exercise in patients with coronary heart disease. 13 Hence, increasing attention has been paid to cardiac rehabilitation after coronary heart disease intervention.…”
Section: Introductionmentioning
confidence: 99%
“…23) Similarly, Tamulevičiūtė-Prascienė, et al examined the effect of resistance and balance training (3 days per week) in patients who underwent valve replacement surgery and found that this intervention improved functional and exercise capacity, physical performance, and muscular strength, and reduced physical frailty levels in the short and medium terms. 24) These study results may imply that functional exercise training, in addition to conventional aerobic exercise and machine resistance training, is important to overcome physical frailty in older patients with heart disease.…”
Section: Functional Exercise Trainingmentioning
confidence: 80%
“…Results from a large cohort study show participation in ebCR to be associated with decreased 1-year cumulative hospitalization, and mortality risk, after valve surgery [ 90 ]. As a result of exercise training (mainly aerobic endurance training), improvements in physical performance, exercise capacity, mobility, and muscular strength have been reported [ 91 , 92 , 93 , 94 , 95 , 96 ].…”
Section: Results and Evidence-based Recommendations For Contents And Application Of Ebcrmentioning
confidence: 99%